Analysis of Long-term Water Quality up to the Standard in Jinchuan River Basin Based on Hydrodynamic and Water Quality Model - CHEN Liming; YU Xin; JIN Zhe; CHEN Chen; CHEN Liangang; WANG Gaoxu (Renmin Zhujiang)
The water quality of the Jinchuan River Basin cannot reach the standard steadily all year round.Thus,after analyzing the pollution characteristics of the basin,this paper proposes three schemes for water quality that can reach the standard in the long term,considering the improvement in the treatment,water supplement,and sewage interception abilities in sewage treatment plans of this basin.Meanwhile,prediction and analysis are also conducted on the water quality improvement effects of each plan.The results are as follows.In current pollution source conditions,regarding the two schemes where sewage treatment efficiency is increased by 10% and the basin water supplement rises by 50% on this basis,the peak concentration of ammonia nitrogen decreases,whereas the concentration is still higher than the Class V water standard.In the third scheme where the inflow concentration can achieve the assessment objectives of a south sewage treatment plant,the pollution load of pollutants into the river is reduced by about 44.4%.Therefore,the ammonia nitrogen concentration in the river network is significantly decreased,and the ammonia nitrogen concentration in the Baotaqiao section of downstream is reduced to 1.85 mg/L.Its water quality can meet the long-term water quality up to the standard in the whole process.The results can provide an effective scientific basis for water pollution control and prevention in the Jinchuan River Basin.